THE EFFECTIVNESS OF E-LEARNING FOR ENGLISH CLASS IN EFL SETTING AND ITS IMPLICATION DURING COVID-19 PANDEMIC - Sutrisna, I Putu Edi; Utami Dewi, Ni Putu Dian (Language and Education Journal Undiksha, 2021)
The English lecturers in EFL countries were urged to consider online teaching and learning when COVID-19 epidemic has spread around the globe. The purposes of this study were: 1) to describe of how English lecturers perceive the e-learning; 2) to describe kinds of e-learning used by English lecturers; and 3) to describe the effectiveness of e-learning from the English lecturers’ perspective. The data analysis covers interview, data reduction, data display and conclusion. It is found that from the English lecturers’ perspectives, e-learning is the use of internet in accessing the virtual classroom learning to engage the students and lectures into the meaningful learning process. The EFL online e-learning instructions are MALL and CALL. The language acquisition process could not be effectively done as the process of e-learning has its limitations (the lack of internet connection from the students’ side). Despite that problems, e-learning classrooms can be helpful during COVID-19 pandemic.